Analisis Kemampuan Keuangan Daerah terhadap Kemiskinan: Studi Empiris di Sumatera Utara - Sodik Dwi Purnomo; Krisnhoe Sukma Danuta (Ekonomis: Journal of Economics and Business, 2022)
Regional Autonomy Policy is intended to improve the performance of regional economic development, in general this policy can spur regional economic growth, but whether the policy is also able to reduce poverty in the region, this situation is the main problem of this study, so this research is aimed at finding out the influence of regional financial capacity on poverty in regencies / cities in North Sumatra province. The data used are secondary data in the form of panels sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK), for 33 districts / cities in North Sumatra province from the period of 2010-2019. The research method uses multiple linear regression. The results showed that ratio of regional financial independence and Degree of Fiscal Decentralization has no significant negative relationship to poverty. Government Expenditure in the Health Sector has a significant negative relationship to poverty. This finding implies that the local government must improve health services as a whole in all districts/cities in North Sumatra Province.